Emergency department resilience to disaster‐level overcrowding: A component resilience framework for analysis and predictive modeling - Davis, Zachary; Zobel, Christopher W.; Khansa, Lara; Glick, Roger E. (Journal of Operations Management, 2020)
Overcrowding poses a serious challenge to the operations of health care facilities, especially those with a mandate to provide emergency care. A better understanding of emergency department (ED) performance during disaster‐level overcrowding is a key to increasing a facility's resilience, optimizing patient outcomes, and more effectively allocating resources. With this in mind, this study quantitatively examines the extent to which different factors contribute to the resilience of hospital EDs during disaster‐level overcrowding events. A modeling framework was developed in collaboration with the Carilion Clinic ED, a level one trauma center in Virginia. The testing and analysis of the approach is based on data from actual disaster‐level overcrowding events that occurred in the Spring of 2016. Results indicate that by considering not only the capacity for resisting such events but also the capacity for recovering from them more quickly, hospital decision makers can improve both their operational effectiveness and the patient experience. Furthermore, by using our framework to identify precipitating factors and predict severe overcrowding, hospital decision makers can implement changes to improve the future resilience of their ED to such overcrowding events.